g(x) = e^(x-1) + x - 6 Show that the equation g(x) = 0 can be written as x = ln(6 - x) + 1, where x<6

0 = ex-1+ x - 6 ex-1 = 6-x x-1 = ln (6-x) -> here we have taken the natural log of both sides, but it only shows on one side as the natural log of e is 1.x = ln (6-x) + 1Question taken from Edexcel 2013 C3 past paper, with my own adapted answer.

Answered by Sumrah N. Maths tutor

6338 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Consider the function F(x)=17(x^4)+13(x^3)+12(x^2)+7x+2. A) differentiate F(x) B)What is the gradient at the point (2,440)


How do you integrate xcos(x)?


Given that y=x/(2x+5) find dy/dx.


Is there an easy way to remember all the basic graphical transformations?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences